Antarctic Clothing (Vestuario Antartico) - Soto,Eduardo Garcia (1976)
By the summer of 1972, the Chilean Antarctic institute (INACH, Instituto Antartico Chileno) had carried out exploratory activities in the Antarctic, preferentially in the coastal zones including studies on the food chains of fishes, benthic communities, tide gauging, etc. Starting in 1973, with the definitive organization of the Glaciological Group, investigations began in this scientific discipline and made necessary going further into the continent, therefore confronting a series of new problems of a logistic variety further requiring penetration, supervision, prevention of risks, ranging inward from the coasts, compulsory self-sufficiency, etc. As a consequence of the above, the requirement exists for making adaptations in clothing as well as a number of modifications in equipment used. Recommendations derived from experimentation are presented. Trans. of Boletin, Instituto Antartico Chileno, n8 p26-28 1975.